Erythromycin-Based Emulgel for Enhanced Anti-Acne Therapy: A Comprehensive Review - Sumedh Prashant Pagare; Dr. Ashish Pawar; Abdul Kalam (Asian Journal of Pharmaceutical Research and Development, 2026)
Acne vulgaris is a chronic inflammatory skin condition affecting about 85 percent of adolescents and a significant percentage of adults across the world, being one of the most common dermatological disorders. Cutibacterium acnes (earlier known as Propionibacterium acnes) causes the disease, due to its ability to colonize the sebaceous follicles and activate innate immunity in the affected area, thus initiating the inflammatory response. Erythromycin, a 14-membered ring macrolide antibiotic, has been successfully used for treatment because of its ability to inhibit bacterial protein synthesis at the level of the 50S ribosome; however, the application of erythromycin in the treatment of acne is largely impeded by several factors, including low aqueous solubility, instability in acid media, increasing drug resistance and poor skin penetrance. Emulgel, a novel drug delivery system which combines an oil-in-water emulsion with a gel base, is being explored as a possible solution to overcome these challenges. Emulgels are effective in increasing the transdermal penetration of erythromycin due to the synergy between the characteristics of emulsion systems, namely better solubilisation of hydrophobic drugs, and gels, including easy application, sustained drug release, and greasy texture. Additionally, the use of advanced drug delivery vehicles such as solid lipid nanoparticles, niosomes, microemulsions, and polymer nanoparticles optimises drug delivery processes and dosage frequencies. This review critically evaluates research findings that have been published between the years 2015 and 2026, covering issues such as physicochemical principles underlying erythromycin action within emulgel formulations, formulation design principles, choice of excipients, characterization methods, in vitro and ex vivo permeability studies, clinical performance evaluations, and regulatory considerations. Issues currently challenging this domain include antibiotic stewardship, monitoring of resistance, stability of formulations, and their scalability to larger scales. Future trends that may be encountered include combination therapy, formulation strategies that spare the skin microbiota, and intelligent stimuli-responsive delivery approaches.